Kemunculan Kaum Fundamentalis Islam sebagai Fenomena Kegagalan Politik Barat - Faizal Zaeni (UIN Sunan Gunung Djati Bandung, 2022)
Islam is a religion that calls for peace. The main Islamic da'wah is peace and love. However, it is quite the opposite if Islam is always associated with various forms of violence today. The violence emerged along with the emergence and development of fundamentalist understanding among religious communities. And then it spread so that it also entered the realm of Islam. So this article will discuss the reasons for the emergence of this understanding, including the failure of Western politics.